2002
DOI: 10.1021/ef020098y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Stability Mechanism of Water-in-Diluted Bitumen Emulsions through Isolation and Characterization of the Stabilizing Materials at the Interface

Abstract: In oil sand industry, formation of a stable salty water-in-diluted bitumen emulsion poses a serious corrosion problem at the bitumen upgrading plant. Previous studies indicated the presence of a "critical concentration" of bitumen in the emulsion, above which the oil-water interface is flexible and the water-in-diluted bitumen emulsion is stable, but below which the interface becomes rigid and the emulsion is unstable. The cause of this critical concentration was investigated through isolation and characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
204
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(226 citation statements)
references
References 40 publications
19
204
0
3
Order By: Relevance
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
“…Wu developed an effective method to collect the interfacial materials (IM) of bitumen which adsorb at the surfaces of heavy water (D 2 O) droplets dispersed in the W/O emulsion. 81 In this method, D 2 O was mixed with heptol (a mixture of heptane and toluene at 1:1 volume ratio)-diluted bitumen to form a stable W/O emulsion. Regular deionized (DI) water was then added in the emulsion, followed by the centrifugation of the resulting mixture.…”
Section: Fractionation Of Asphaltenes Based On Asphaltene Adsorptionmentioning
confidence: 99%
“…Competitive interaction of those species at the water-oil interface has been considered by several researchers, 3,8,9,10 while the introduction of resins has been shown to soften or increase the flexibility of an asphaltene interfacial film. 3,11 When studying micron-sized water drops immersed in diluted bitumen, Wu 12 considered the response of interfacial films to drop volume reduction. At low (solvent:bitumen) dilution ratio, the drop shape was maintained during withdrawal of water, while at high dilution ratio, the interfacial material offered resistance to in-plane shear as observed by drop crumpling.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions and assembly of adsorbed molecules or their aggregates lead to formation of a protective layer that resists droplet-droplet coalescence. [1][2][3][4][5][6][7][8][9][10][11] Stable emulsions have been a major challenge in petroleum production, affecting process throughput and downstream operations such as upgrading. It is necessary to develop knowledge on the formation of these protective layers to design suitable protocols for film disruption and prevention of stable emulsion formation.…”
Section: Introductionmentioning
confidence: 99%